Epigenetic Treatment of Neurodegenerative Disorders: Alzheimer and Parkinson Diseases. Issue 3 (21st February 2016) - Irwin, Michael H.; Moos, Walter H.; Faller, Douglas V.; Steliou, Kosta; Pinkert, Carl A.
Abstract: Preclinical Research In this review, we discuss epigenetic‐driven methods for treating neurodegenerative disorders associated with mitochondrial dysfunction, focusing on carnitinoid antioxidant‐histone deacetylase inhibitors that show an ability to reinvigorate synaptic plasticity and protect against neuromotor decline in vivo. Aging remains a major risk factor in patients who progress to dementia, a clinical syndrome typified by decreased mental capacity, including impairments in memory, language skills, and executive function. Energy metabolism and mitochondrial dysfunction are viewed as determinants in the aging process that may afford therapeutic targets for a host of disease conditions, the brain being primary in such thinking. Mitochondrial dysfunction is a core feature in the pathophysiology of both Alzheimer and Parkinson diseases and rare mitochondrial diseases. The potential of new therapies in this area extends to glaucoma and other ophthalmic disorders, migraine, Creutzfeldt–Jakob disease, post‐traumatic stress disorder, systemic exertion intolerance disease, and chemotherapy‐induced cognitive impairment. An emerging and hopefully more promising approach to addressing these hard‐to‐treat diseases leverages their sensitivity to activation of master regulators of antioxidant and cytoprotective genes, antioxidant response elements, and mitophagy. Drug Dev Res 77 : 109‐123, 2016. © 2016 Wiley Periodicals, Inc.